Promising Parental Cowpea Genotypes With Resistance to Aphid (Aphis craccivora Koch) Biotypes in Uganda - Selma Ndapewa Nghituwamhata; Ephraim Nuwamanya; Richard Edema; Faizo Kasule; Chepkoech Evalyne Rono; Arfang Badji; Albert Chiteka; Isaac Onziga Dramadri (wiley, 2025)
Cowpea aphids remain a major production constraint affecting productivity on smallholder farms in Uganda. This study aimed to identify cowpea genotypes with resistance to aphid biotypes in Uganda for developing improved cowpea varieties. Forty-eight cowpea genotypes were initially screened using aphids collected at Makerere University Agricultural Research Institute Kabanyolo (MUARIK), and 10 tolerant genotypes were further screened using three aphid biotypes collected from the three experimental stations, namely, MUARIK, NgettaZARDI, and NaSARRI, representing the major cowpea production regions. All experiments were laid out in a completely randomized design (CRD) with three replications in the screen house at MUARIK under free-choice conditions in the screen house at MUARIK (25°C–28°C, 65%–80% relative humidity) and a natural 12:12 h light–dark regime. Significant differences were observed among the cowpea genotypes for aphid infestation and damage (aphid counts, colony scores, and leaf damage) and growth response (days to 50% flowering). There were no significant differences in the response of genotypes to aphids collected from the three locations representing Uganda’s diverse agroecologies. Sanzi, TVNu 1158 (wild relative), and NE 51 showed high levels of resistance to the aphid biotypes and can be used as parents for developing aphid-resistant cowpea varieties in Uganda. However, genotype Tvu 310, the resistant check from IITA, was found to be susceptible, while IT97K-556-6 was moderately resistant to aphid biotypes from Uganda. The results from this study provide an understanding of resistance to aphid biotypes, and resistant cowpea genotypes can be used as a source for resistance to aphids in Uganda.
Keywords: aphids; biotypes; resistant varieties